2015
DOI: 10.1007/s00345-015-1720-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sexual dysfunction in men with chronic prostatitis/chronic pelvic pain syndrome: a meta-analysis

Abstract: PurposeThis study aims to estimate the prevalence of sexual dysfunction in men with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) by conducting a meta-analysis.MethodsRelevant publications were searched using PubMed, Embase, CBM, China National Knowledge Infrastructure, VIP and Wanfang databases up to August 2015. Studies that reported the prevalence of erectile dysfunction, premature ejaculation and total sexual dysfunction in men with CP/CPPS were included.ResultsA total of 24 studies involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 29 publications
0
51
0
4
Order By: Relevance
“…Sexual dysfunction is often associated with prostatitis though limited studies claim that there is still some controversy. Our team had conducted a pooled study which showed that the prevalence of sexual dysfunction for adult males with chronic prostatitis was high up to 62% [ 17 ]. ED is one of the most common types of sexual dysfunction; previously, a meta-analysis found that cases with chronic prostatitis have an increased risk of ED compared the control group (pooled OR 3.02, 95% CI: 2.18–4.17) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dysfunction is often associated with prostatitis though limited studies claim that there is still some controversy. Our team had conducted a pooled study which showed that the prevalence of sexual dysfunction for adult males with chronic prostatitis was high up to 62% [ 17 ]. ED is one of the most common types of sexual dysfunction; previously, a meta-analysis found that cases with chronic prostatitis have an increased risk of ED compared the control group (pooled OR 3.02, 95% CI: 2.18–4.17) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although men with lifelong and acquired PE appear to share the dimensions of short ejaculatory latency, reduced ejaculatory control, and the presence of negative personal consequences, Men with acquired PE are older, have higher incidences of erectile dysfunction, comorbid disease, and cardiovascular risk factors, and have a longer intravaginal ejaculation latency time (IELT) as compared with men with lifelong PE 23 . Acquired PE is commonly due to sexual performance anxiety 24 , erectile dysfunction (ED) 25 , and occasionally prostatitis 26 or hyperthyroidism 12 . Because of the heterogeneous physiology of ejaculation and pathophysiology of different types of PE, the present study only evaluated the patients with lifelong PE.…”
Section: Discussionmentioning
confidence: 99%
“…Pain is another common complaint of methadone-maintained patients, which refers to “an unpleasant sensory and emotional experience associated with actual or potential tissue damage, or described in terms of such damage.” 13 – 16 Due to concerns about opioid dependence as a barrier to pain management, pain is also often undertreated or untreated in addiction treatment practice. 13 , 17 Previous studies have reported a high prevalence of sexual dysfunction in patients with painful conditions (ie, chronic pelvic pain syndrome and chronic low back pain), 18 20 which is particularly high among those with intensive and severe pain. 20 Therefore, we speculate that pain is associated with sexual dysfunction in methadone-maintained patients.…”
Section: Introductionmentioning
confidence: 99%